Painless childbirth - Lamaze, Fernand (Chicago, 1970)
A guide to the Lamaze method of childbirth, focusing on natural, pain-reducing techniques through breathing exercises, relaxation, and psychological preparation. The book explains how expectant mothers can manage labor with minimal medical intervention, emphasizing education, partner support, and confidence during childbirth.
Keywords: Childbirth; Natural childbirth; Pregnancy care